New automatic impulse extinguishing device - Suslavičius, Vladimiras; Bogdevičius, Marijonas (Transport, 2008)
A simple way to increase the extinguishing water surface area is to atomize water into fine drops. The smaller drops are developed, the better use of water properties can be implemented and less water is consumed in fire fighting. The automatic impulse extinguishing is created. The main aim of the investigation is to develop the approach to investigate the dynamic and hydrodynamic processes in the extinguishing device. The mathematical model of the extinguishing device is presented, where the flow of liquid and gas and the interaction of liquid with the gas are taken into account. The flow of fluids in a hydraulic system is described by a system of equations of a hyperbolic type, which is solved by a characteristics method. An instance of the mathematical simulation of the activity of extinguishing device is shown. First published online: 27 Oct 2010